2018
DOI: 10.1002/ccd.27463
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term pacemaker dependency and impact of pacing on mortality following transcatheter aortic valve replacement with the LOTUS valve

Abstract: Only 38% of Lotus recipients who require a PPM following TAVR with the Lotus valve remain pacing dependent at one year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In cohort studies of patients receiving a mix of TAVR prostheses, long-term dependency ranged from 27% (68) to 68.4% (69). A study in patients receiving CoreValve self-expandable valve showed a 46.7% long-term dependency (70), whereas in a cohort of patients undergoing TAVR with a Lotus valve, 57% and 38% of patients were pacemakerdependent at 30-day and 1-year, respectively (71). Thus, a transient effect of inflammation, edema, ischemia or direct injury may show a subsequent recovery in a substantial number of patients, suggesting a short period of rhythm monitoring could be advisable before PPM is implanted after TAVR, in order to avoid unnecessary PPM when attempting to shorten hospital stays.…”
Section: Permanent Pacemaker Implantationmentioning
confidence: 99%
“…In cohort studies of patients receiving a mix of TAVR prostheses, long-term dependency ranged from 27% (68) to 68.4% (69). A study in patients receiving CoreValve self-expandable valve showed a 46.7% long-term dependency (70), whereas in a cohort of patients undergoing TAVR with a Lotus valve, 57% and 38% of patients were pacemakerdependent at 30-day and 1-year, respectively (71). Thus, a transient effect of inflammation, edema, ischemia or direct injury may show a subsequent recovery in a substantial number of patients, suggesting a short period of rhythm monitoring could be advisable before PPM is implanted after TAVR, in order to avoid unnecessary PPM when attempting to shorten hospital stays.…”
Section: Permanent Pacemaker Implantationmentioning
confidence: 99%
“…The analysis reported VpDep rates of 43% and 50% at 1 month and 1 year respectively. In a trial evaluated the incidence of VpDep following Lotus valve implantation, 3 a cut point of 40 bpm was used to define VpDep. At 30-day and 1-year, 57% and 38% were pacing dependent respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to investigate the impact of PPM implantation on long-term outcomes before the indications for TAVR are expanded to include lower risk populations, as the follow-up duration in most included studies was not long enough to show the deleterious effects of PPM implantation. In addition, more than half of the patients implanted with a PPM after TAVR were not pacemaker dependent, while pacemaker dependency is a predictor of heart failure (42).…”
Section: Discussionmentioning
confidence: 99%